Dietary transformations and health implications in migrant populations: a global perspective - Varre, Joseph Vinod; Dustin, Mia; Van Vliet, Stephan (Frontiers in Nutrition, 2025)
BackgroundDietary acculturation—the process by which migrants adopt the dietary patterns of their host country—has become increasingly relevant given the unprecedented scale of international migration. This phenomenon is often associated with a shift from traditional diets toward host-country patterns that are higher in ultra processed foods, added sugars, and fats, with potential implications for chronic disease risk.ObjectiveThis mini-review aims to synthesize global evidence on the dietary transformations experienced by migrant populations and to assess the health implications and modulating factors influencing these changes.MethodsA targeted literature search was conducted in PubMed, Scopus, and Web of Science for articles published between January 2000 and April 2024, using keywords related to dietary acculturation, migration, and health outcomes. After applying inclusion and exclusion criteria, 30 studies directly addressing dietary change and health outcomes post-migration were included. Key themes were identified through iterative synthesis.ResultsEvidence indicates a consistent trend of dietary acculturation across diverse migrant groups, typically involving increased consumption of energy-dense, processed foods (a 15–20% increase) and decreased intake of traditional staples such as whole grains (down by 10–15%), pulses, and fresh vegetables. These dietary shifts are associated with a heightened risk of obesity (increasing by 5–10%), type 2 diabetes (7–12% rise), and cardiovascular diseases. Factors such as length of residence (1–5 years), age at migration (20–30 years), socioeconomic status (bottom 20%), food environment (availability dropping by 30%), and health literacy significantly modulate these changes. Emerging evidence also points to changes in gut microbiota as a consequence of dietary transformation.ConclusionDietary acculturation among migrant populations is a multifaceted process that increases the risk of nutrition-related chronic diseases. There is a critical need for culturally sensitive public health interventions and policies that support the preservation of healthy traditional diets while facilitating healthy adaptation to new food environments. Addressing research gaps—such as longitudinal data and the experiences of underrepresented migrant groups—will strengthen strategies to mitigate adverse health outcomes.